An antibody against Siglec-15 promotes bone formation and fracture healing by increasing TRAP+ mononuclear cells and PDGF-BB secretion - Gehua Zhen (Nature Publishing Group, 2021)
Abstract Osteoporosis (OP) is a common age-related disease characterized by a deterioration of bone mass and structure that predisposes patients to fragility fractures. Pharmaceutical therapies that promote anabolic bone formation in OP patients and OP-induced fracture are needed. We investigated whether a neutralizing antibody against Siglec-15 can simultaneously inhibit bone resorption and stimulate bone formation. We found that the multinucleation of osteoclasts was inhibited in SIGLEC-15 conditional knockout mice and mice undergoing Siglec-15 neutralizing antibody treatment. The secretion of platelet-derived growth factor-BB (PDGF-BB), the number of tartrate-resistant acid phosphatase-positive (TRAP+) mononuclear cells, and bone formation were significantly increased in the SIGLEC-15 conditional knockout mice and antibody-treated mice. The anabolic effect of the Siglec-15 neutralizing antibody on bone formation was blunted in mice with Pdgfb deleted in TRAP+ cells. These findings showed that the anabolic effect of the Siglec-15 neutralizing antibody was mediated by elevating PDGF-BB production of TRAP+ mononuclear cells. To test the therapeutic potential of the Siglec-15 neutralizing antibody, we injected the antibody in an ovariectomy-induced osteoporotic mouse model, which mimics postmenopausal osteoporosis in women, and in two fracture healing models because fracture is the most serious health consequence of osteoporosis. The Siglec-15 neutralizing antibody effectively reduced bone resorption and stimulated bone formation in estrogen deficiency-induced osteoporosis. Of note, the Siglec-15 neutralizing antibody promoted intramembranous and endochondral ossification at the damaged area of cortical bone in fracture healing mouse models. Thus, the Siglec-15 neutralizing antibody shows significant translational potential as a novel therapy for OP and bone fracture.